ANALISIS INTERDEPENDENSI NILAI TUKAR, INFLASI, PRODUK DOMESTIK BRUTO, SUKU BUNGA DAN NERACA TRANSAKSI BERJALAN DI INDONESIA - Uline Afriany Prasetia Simarmata (Universitas Negeri Medan, 2012)
Depreciation of the rupiah prompted Bank Indonesia raised SBI to strengthen the rupiah, inflation has a downward trend when the appreciation of the rupiah, and the movement of the exchange rate also change the position of the current account of Indonesia. This study aimed to determine the role and effects of changes in exchange rates, inflation, gross domestic product, interest rates and the current account balance for each variable. Data obtained from secondary data is exchange rate, inflation, GDP, interest rates and the current account data from 2000:1 up to 2010:4. The model used in this study is the econometric model by the method of Vector Autoregressive (VAR) that in their analysis the instrument has Impulse Response Function (IRF) and Variance Decomposition (VD). The results of this study concluded that (1) All variable giving each other random shock to other variables and response by each variable so as to achieve long-term equilibrium. This is shown on the estimation IRF test on each variable; (2) All variables are mutually contribute to other variables. It is shown by the results of estimation VD test, in which each variable contributed to other variables.